Evaluating the effectiveness of a verbal autopsy workshop: A comparative analysis of pre- and posttest - Neeraj Agarwal; Neha Chaudhary; Shamshad Ahmad; Pankaj Kumar Pathak (Wolters Kluwer Medknow Publications, 2021)
Introduction: AIIMS Delhi developed an online platform Mortality in India established through Verbal Autopsies, which ultimately provides data on the cause of death in the country. AIIMS Patna being one of the partner institutions in this initiative of AIIMS Delhi, thus, conducted a 2-day workshop of Registrar General of India supervisors with the objective to strengthen the knowledge of participants and improve their practices on writing a good narrative during verbal autopsy (VA) using a key symptom list. Materials and Methods: A total of 32 participants attended the 2-day workshop at the Department of Community and Family Medicine, AIIMS Patna, in January 2019. A pretest questionnaire was administered before the start of the workshop and to test the improvement in knowledge of participants after attending the workshop, the same questionnaire was again administered as a posttest at the end of the workshop. Feedback of participants was also collected on a predesigned semi-structured questionnaire. The collected responses were entered in MS Excel 2010. Descriptive and inferential statistics were calculated using SPSS version 16.0 software. Results: There was a statistically significant improvement (P < 0.001) in the mean posttest score (8.6 ± 1.2) as compared to the mean pretest score (6.1 ± 2.8). Maximum participants, i.e., 15 (46.8%), reported that filling VA forms in a narrative way was the most useful part of the workshop. All the participants, i.e., 32 (100%), strongly agreed that the workshop was appropriately organized, content of the training was relevant, they were encouraged to actively participate, and adequate material was provided. Conclusion: Further intensive workshop with more field training and refresher training at regular intervals is expected in future.